Teori-Teori Belajar dan Kaitannya Dengan Pengembangan Kurikulum PAI - Hayati, Mufidah; Murdiana, Murdiana; Arifmiboy, Arifmiboy (ANTHOR: Education and Learning Journal, 2023)
Signs of learning people can be seen and the occurrence of transformations within a person Transformation is a change in behavior Changes in behavior touch 3 educational domains within the learner, namely cognitive abilities, affective domains, and psychomotor domains or better known as knowledge domains, attitude domains, and domain of skills So and that requires situations and conditions of teaching and learning activities that support, available facilities, and so on must be adjusted to the educational goals to be achieved This study aims to find out the learning theory that must be known by teachers and students so that learning objectives can be achieved effectively and efficient This research is "Library Research" with a research approach to text literacy and field phenomena. Methods and types of data collection by collecting journals that support the research theme. The data stages are from identifying and finding information that is relevant to the theme of learning theory, its implications in PAL learning, then analyzing the findings. Data processing is carried out by carrying out activities of review, verification and reduction, grouping and systematization , as well as interpretation or interpretation so that a phenomenon has social, academic and scientific meaning. Meanwhile, data analysis in this study was carried out during and after data collection using a critical-comparative descriptive method and content analysis method. to improve the quality of learning, as well as convey teaching materials to students so that they can be understood besides that teachers want to make the teaching process functional, this means that a teacher must master how learning theories to find out what is needed by students, also at the same time will help students in developing the world